Molecular Detection of Histoplasma capsulatum in Antarctica - Lucas Machado Moreira; Wieland Meyer; Márcia Chame; Martha Lima Brandão; Adriana Marcos Vivoni; Juana Portugal; Bodo Wanke; Luciana Trilles (Emerging Infectious Diseases, 2022)
We detected Histoplasma capsulatum in soil and penguin excreta in the Antarctic Peninsula by sequencing after performing species-specific PCR, confirming previous observations that this pathogen occurs more broadly than suspected. This finding highlights the need for surveillance of emerging agents of systemic mycoses and their transmission among regions, animals, and humans in Antarctica.